ESRD and ESRD-DM associated with lignite-containing aquifers in the U.S. Gulf Coast region of Arkansas, Louisiana, and Texas - Ojeda, Ann S. (Int J Hyg Environ Health, 2018)
Balkan endemic nephropathy (BEN) is an irreversible, lethal kidney disease that occurs in regions of the Balkans where residents drink untreated well water. A key factor contributing to the development of BEN may be consumption of dissolved organic matter leached from low-rank coal called lignite. This hypothesis—known as lignite-water hypothesis—was first posed for areas of the Balkans. It is possible that a BEN-like condition exists in the United States (US) Gulf Coast region in parts of the Mississippi Embayment and the Texas Coastal Uplands aquifers —Arkansas, Louisiana, and Texas, for instance—that rely heavily on groundwater from aquifers that contain lignite. This paper utilizes a geographic information system (GIS) to map the distributions of end-stage renal disease (ESRD) in relation to water from lignite-containing aquifers in the tri-state region. Regional patterns emerged from geospatial analysis, indicating that counties that relied on lignite-containing aquifers for their main water source had higher rates of ESRD in comparison to other populations in the state that rely on other water sources, including surface water and groundwater from aquifers not associated with lignite seams. Statewide rates of ESRD and diabetes associated ESRD (ESRD-DM) showed strong correlations to the percent of families at or below poverty level and the percentage of African Americans. These confounding factors somewhat mitigate the association seen between ESRD and lignite-containing regions at the state level. However, at the larger tri-state view, there is a significant (p = 0.002) increase in incidence rates when considering both race and poverty. Additionally, no relationship was observed between the rate of public water supply withdrawal from lignite-bearing aquifers and rates of ESRD or ESRD-DM at the state or tri-state regions, supporting the observation that the risk associated with water from lignite-containing aquifers is limited to water from untreated domestic supply.